English Instruction Practices of Pre-service Physical Education Students at Dehasen University Bengkulu - Putra, Aziiz Rahman; Pradana, Ami; Putra, Dhanu Ario; Dewa, Barata Harsena (Langue (Journal of Language and Education), 2025)
Grounded in Pedagogical Content Knowledge (PCK) and Second Language Acquisition (SLA) principles, this study examines the English instruction practices of pre-service Physical Education (PE) teachers at Dehasen University Bengkulu during action-based lessons, focusing on instruction types, adaptive strategies, and challenges. A descriptive qualitative design was applied with 18 final-year PE students selected through purposive sampling. Data were collected via classroom observations, semi-structured interviews, and lesson plan analysis, and analyzed thematically. Findings show that teachers primarily used verbal commands, such as “Pass the ball!”, “Run to the cone”, and “Stretch your arms”, often supported by visual demonstrations, gestures, and combined verbal-gestural strategies, particularly during fast-paced drills. Adaptive techniques, including vocabulary simplification (“Kick” instead of “Perform a kick”), repetition (“Jump twice, jump twice”), pausing, and selective code-switching (using Indonesian for clarification), facilitated student comprehension. Challenges included limited English proficiency, fast-paced activities, and balancing classroom management with instruction delivery. The study underscores the importance of reflective practice, multimodal instruction, and targeted pre-service training, providing insights for effective English instruction in EFL PE contexts.